Standardised Andrographis paniculata Burm. Nees extracts and andrographolide prevent airway inflammation in house dust mite and diisocyanate- induced asthma models - Sulaiman, Ibrahim (2018)
The therapeutics of asthma is commonly based on the use of steroids and bronchodilators. However, steroid-sensitive asthmatics are at the risk of debilitating side effects associated with persistent use of steroids. There is, therefore, the need for discovery and development of better and safer alternatives. Andrographis paniculata (AP) is traditionally used as a herbal remedy to a wide range of inflammatory conditions. Its anti-inflammatory activity is attributable to its major diterpenoid, andrographolide (AGP). Anti-asthma activity of AGP was previously reported in ovalbumin mouse asthma model. This study investigated the anti-asthma potential of standardised Andrographis paniculata aqueous extract (APAE) and aqueous ethanolic extract (APEE50) in house dust mite (HDM) induced asthma. In addition, the efficacy and mechanism of action of AGP in the prevention of airway inflammation and oxidative stress in toluene diisocyanate (TDI)-induced occupational asthma (OA) model were evaluated. The extracts were standardised based on percentage distribution of AGP, neoandrographolide (NAG) and 14-deoxy-11,12- didehydroandrographolide (DDAG). The AGP, NAG and DDAG contents of standardised APAE were approximately 3.4%, 1.1% and 0.1% (w/w), while that of APEE50 were 8.7%, 1.4% and 0.3% (w/w) respectively. APAE was proven to inhibit NF-κB p65 signalling pathway in a TNF-α-exposed A549 bronchial epithelial cell line without inducing cytotoxicity. The inhibition of p65 signalling pathway occurred by preventing IKK phosphorylation, IĸB-α activation, p65 nuclear translocation and DNA binding activity of p65. In vivo analysis of APAE and APEE50 activity in 14 days HDM-induced asthma model recorded substantial improvement in asthma markers. Treatments were administered following a prophylactic regimen. Both treatments significantly decreased bronchoalveolar lavage fluid (BALF) total and differential leukocyte count at a dose range of 50 – 200 mg/kg. A significant reduction in BALF IL-4, IL-5, IL-13, and eotaxin, as well as HDM-specific IgE, total serum IgE and IgG were recorded. Histopathological analysis of lung samples showed a remarkable reduction in perivascular and peribronchial inflammation, as well as suppression of mucus production by both APAE and APEE50. A dose-dependent decrease in airway resistance and a slight increase in dynamic lung compliance were witnessed. Notably, the expression of NF-κB transcribed genes, Th2 inducible genes and eosinophil modulating genes were decreased, while Nrf2 gene was concomitantly upregulated. Diisocyanate-induced asthma presented airway inflammation of neutrophilic endotype. The administration of AGP (0.1, 0.5 and 1 mg/kg) produced progressive decreased in airway inflammation parameters. In addition to suppression of airway cellular infiltration and mucus production, collagen deposition was deterred by the treatments. TDI exposure induced an aberrant distribution of E-cadherin and β- catenin in airway epithelia. AGP ameliorated the loss of airway integrity by restoring normal distribution of E-cadherin and β-catenin. The mechanism of action of AGP in TDI-induced asthma occurred through ROS scavenging and up-regulation of the pulmonary HO-1 level via p38/Akt/GSK-3β/Nrf2 dependent pathway. The expression of both Th1 and Th2-related genes were downregulated in AGP treated animals. Furthermore, TDI-induced airway hyperreactivity was improved by AGP administration. These findings strongly suggest that AGP and AP extracts could serve as potential alternative treatments for chemical and nonchemical-induced asthma respectively.